El derecho de la OIT en las demandas individuales presentadas ante el Tribunal Europeo de Derechos Humanos - Sanz Rubiales, Susana (Revista de Derecho, 2019)
This article shows the most social side of the European Court of Human Rights through the location and legal analysis of those judgments in which either the parties or the Court itself, have invoked the work and standards of the International Labour Organization. This aspect of the Strasbourg Court case law is poorly understood because the rights that the European Convention on Human Rights includes are of a civil and political character. However, the Court has used several techniques in order to protect economic and social rights. The use of these techniques has allowed the development of a social case law which is primarily based on five provisions of the Convention: the prohibition of forced labour, the right to respect for private and family life, the freedom of expression, the freedom of assembly and association and the prohibition of discrimination. In a number of these judgments the Court has used the ilo Law as a reference and guide due to the organization’s specialization in the protection of labour rights.